Peran Wakaf Sebagai Instrumen Kekayaan Islam Untuk Pengetasan Kemiskinan Di Indonesia: Studi Kasus Tahun 1999 -2018 - Mareta Fitriyani; Muhammad Habibi; Muhammad Abdul Rohman; Nurfala Safitri (Asyafina Akademik Press, 2022)
The purpose of this study is to explain the evidence that waqf can reduce poverty in Indonesia. This study uses an ordinary least square approach as pool analysis and fixed effect model. The data used is district/city level data in Indonesia from 1999 to 2018. The results show that the more waqf land in Indonesia, the lower the poverty rate in urban districts. Then the number of certified waqf lands also affects poverty reduction in Indonesia. Then the number of uncertified waqf land does not have a strong effect on reducing poverty. This calls for policymakers that waqf management in Indonesia is quite effective in alleviating poverty Repository Data: Asyafina Journal Dataverse powered by Hardvard University